2019
DOI: 10.11591/eei.v8i2.1527
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient smart street light for smart city using sensors and controller

Abstract: Smart street light is an intelligent control of street lights to optimize the problem of power consumption of the street, late in night. Conventional street lights are being replaced by Light Emitting Diode (LED) street lighting system, which reduces the power consumption. The focus of this project is to design a system of street lights controller to provide a reduction in power consumption. The prototype was designed by using Light Dependent Resistor (LDR), Infrared sensor (IR), battery and LED. The brightnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…The light and darkness of the lights depended on the speed of the detected object movement. The results showed that the system had a good energy-saving effect [14] .…”
Section: Related Workmentioning
confidence: 98%
“…The light and darkness of the lights depended on the speed of the detected object movement. The results showed that the system had a good energy-saving effect [14] .…”
Section: Related Workmentioning
confidence: 98%
“…By crafting a miniature replica of a smart LED streetlight system and implementing sensor-based dimming technology, experimental insights into light-dimming controls can be garnered [16,17]. Moreover, time-based dimming experiments can offer valuable insights into the energy efficiency correlated with streetlight operations [18,19].…”
Section: Literary Reviewmentioning
confidence: 99%
“…In this scheme, brightness adjusts based on user presence, turning lamps ON as users approach and dimming them afterwards [67,[69][70][71]. The optimization of this light scheme can be furthered by measuring speed, such as calculating the average speed between two IR sensors, allowing for the categorization of road users and the application of suitable zoning light profiles [72].…”
Section: Simple Rule-based Controlmentioning
confidence: 99%